Néstor García Canclini: El enfoque cultural de la comunicación. (Chasqui (13901079), 2009)
The article provides a profile of Argentine anthropologist Néstor García Canclini. The author offers a detailed description of García Canclini's home and workplace in Mexico City, Mexico, discusses the various professorships he has held at universities such as the Universidad Autónoma Metropolitana de México and Stanford University, and comments on the significance of his book “Culturas híbridas.” The concept of hybridity is described as García Canclini applies it to the analysis of cultural processes, mass media, and forms of communication.